The Confucius’ Traces in Current Chinese University Teaching - Redondo Martínez, José Carlos (Sinología hispánica. China Studies Review, 2020)
The study in-depth of The Analects gives us an idea of how the Confucius’ ideas for society were. The Master always advocated bringing social reforms through the education of individuals in society. He wanted to develop an ideal social order through the cultivation of ideal lifestyles and the full development of the personality of the individuals. Through years of experience and the thorough analysis of the behaviour of Chinese teachers and students when teaching and learning it has been shown that the main principles of Confucian teachings are still present in crucial figures such as the teacher, the class monitor and the students; as well as in several factors that determine the teaching such as motivation, the teacher's reprimand, the students’ shyness and the memorization of concepts. Furthermore, it is particularly important to compare the European teacher with the Chinese one, since the former is mainly influenced by the Greco-Roman philosophy and the thinkers of the Enlightenment; the latter is tremendously influenced by the ideas of Confucius despite the fact that they were born more than 2,500 years ago.